As boas práticas de maneio da água em suinicultura, como factor limitante para uma gestão correcta e uso dos chorumes animais como fertilizante - um exemplo com maternidades e gestações - Ferreira, L. (2011)
The aim of this work was to demonstrate in commercial pig farms focused in the lactation and gestation production stages, the importance to adopt good management practices for water use on the value of slurry as fertilizer. It was performed during 18 month a field study, involved four farrow-to-finishing units. During this period its was evaluated the water consumption and slurry production associated to the sows lodged in lactation and gestation phases of production, as well as the composition of the slurries produced. Based on these results it was possible to establish water consumption and slurry production ratios per animal according to lodging, drinking and feeding equipment systems. It was concluded that slurries characteristics are influenced by the water management inside the production units, therefore the fertilizer value potential is also affected. With this regard, the required storage capacity infrastructure can be conditioned and the necessary optimization of the investments penalized in function of the nutrients concentration. For the Portuguese reality, a storage capacity cost of 0,10 - 0,16 € / kg N , is expected respectively for slurries with 2,5 g N/l to 1,5 g N/l .